Reactions of t-Boc-Protected Amines with Difluorocarbene - Gerasov, Andrii; Shivanyuk, Alexander; Fetyukhin, Volodymyr; Lukin, Oleg (Synthesis, 2019)
The reactions of t-Boc-protected secondary and primary amines with difluorocarbene generated from trimethylsilyl (fluorosulfonyl)difluoroacetate [Me3SiOC(O)CF2SO2F] (TFDA) in toluene at 110 °C results in the replacement of t-Bu by difluoromethyl in the t-Boc group. This reaction can be carried out in the presence of CH2Br and COOMe moieties in the structure of the protected amine. In the example of a t-Boc-protected amine containing a C=C double bond, replacement of the t-Bu group and/or cyclodifluoropropanation takes place. Difluoromethyl esters are shown to react with primary and secondary amines yielding the corresponding ureas.
Keywords: t-Boc group; trimethylsilyl (fluorosulfonyl)difluoroacetate; t-Bu/CHF2 replacement; difluoromethylcarbamate; acylation; urea